Paul's theology of preaching : the Apostle's challenge to the art of persuasion in ancient Corinth - Litfin, A. Duane (Downers Grove, Illinois : IVP Academic, 2015)
"This revised and expanded version of Litfin's previous St. Paul's Theology of Proclamation will provide insight to those engaged in Pauline and New Testament studies, rhetorical theory and Greco-Roman studies. Moreover, by offering a better understanding of Paul's method as well as the content of his declaration concerning 'the power and wisdom of God' revealed in Jesus, this book will help preachers as they 'preach Christ crucified.'" -- Back Cover
Part one : Greco-Roman rhetoric. The beginnings ; The goal of rhetoric ; The power of rhetoric ; The reach of rhetoric ; The genius of rhetoric ; The appraisal of rhetoric ; The hazards of rhetoric ; The rewards of rhetoric ; The grand equation of rhetoric -- Part two : 1 Corinthians 1-4. Paul and rhetoric in Corinth ; The setting of 1 Corinthians 1-4 ; Paul's argument introducted : 1 Corinthians 1:1-17 -- Paul's argument begun : 1 Corinthians 1:17-20 -- Paul's argument encapsulated : 1 Corinthians 1:23 -- Paul's argument continued : 1 Corinthians 1:22-2:5 -- Paul's argument completed : 1 Corinthians 2:6-4:21 -- Part three : summary and analysis. Paul's ministry model ; Important questions ; Appropriate strategies ; Conclusion : the Pauline model -- Appendix one : Paul, Apollos and Philo -- Appendix two : the book of Acts -- Appendix three : Paul's epistemology -- Appendix four : implications for preaching ; Appendix five : broader implication.
"Original edition copyright 1994, by Duane Litfin, published by Cambridge University Press under the title St. Paul's theology of proclamation : 1 Corinthians 1-4 and Greco-Roman rhetoric, Vol. 79 in the Society for New Testament studies monograph series"--Title page verso.
Includes bibliographical references (pages 360-386) and indexes.
Keywords: Bible -- Criticism, interpretation, etc; Preaching -- Biblical teaching; Rhetoric, Ancient; Rhetoric in the Bible